Relative effects of land conversion and land-use intensity on terrestrial vertebrate diversity - Philipp Semenchuk; Christoph Plutzar; Thomas Kastner; Sarah Matej; Giorgio Bidoglio; Karl-Heinz Erb; Franz Essl; Helmut Haberl; Johannes Wessely; Fridolin Krausmann; Stefan Dullinger (Nature Communications, 2022)
Land use is a major driver of biodiversity loss, but disentangling the contribution of its various components is challenging. Here, the authors partition the role of land use type and intensity in explaining global patterns of impending species losses for terrestrial vertebrates.